Basic bases of calculations and optimization of NPP power unit equipment parameters methods of mathematical modelling - Yefimov, Olexander Vyacheslavovych; Ilchenko, Boris Samuilovich; Tiutiunyk, Larysa Ivanivna; Harkusha, Tetyana Anatoliivna; Yesipenko, Tetyana Oleksiivna; Motovilnik, Anastasiia Vadimovna (Національний технічний університет "Харківський політехнічний інститут", 2021)
The materials of the article consider the optimization of certain parameters and characteristics of the equipment of NPP power units, which are closely related to the processes of their design and construction. Modern NPP power units are complex technical systems. They include a set of interconnected equipment for different technological purposes, which ensures the performance of power units of a complex function of electricity production and heat of the specified quality and according to a given load schedule. Complete mathematical models of the functional state of steam turbine power units are characterized by a large number of nonlinear connections and contain implicit functions. This complicates their widespread use to solve problems of systematic analysis of the quality of operation of power units. The aim of the work is to analyze the basic theoretical foundations, methods and approaches to the calculation and optimization of the parameters of the equipment of NPP power units by methods of mathematical modeling. The solution of the problem of optimization of NPP power unit parameters includes the following stages: selection of optimality criteria (objective functions); development of a system of interconnected mathematical models in accordance with the required hierarchical level of optimization research; selection of computational methods and optimization algorithms. Taking into account the above methodological provisions and approaches increases the efficiency of mathematical modeling to solve problems of calculations and optimization of NPP power unit parameters.

У матеріалах статті розглянуті базові основи розрахунків та оптимізація окремих параметрів і характеристик устаткування енергоблоків АЕС, які тісно пов’язані з процесами їх проектування і конструювання. Сучасні енергоблоки АЕС є складними технічними системами. Вони включають до себе безліч взаємопов'язаного між собою устаткування різного технологічного призначення, що забезпечує виконання енергоблоками складної функції виробництва електричної енергії та теплоти встановленої якості і за заданим графіком навантаження. Повні математичні моделі функціонального стану паротурбінних енергоблоків АЕС характеризуються великою кількістю нелінійних зв’язків і містять неявні функції. Це ускладнює методи та принципи їх математичного моделювання і обумовлює застосування спеціальних принципів та підходів.
Базові основи розрахунків та оптимізації параметрів устаткування енергоблоків АЕС методами математичного моделювання
Keywords: NPP power unit equipment; parameter optimization; устаткування енергоблоків АЕС; оптимізація параметрів